ANALISIS SELF ESTEEM DAN SELF TRANSCENDENCE PERFORMA SISWA SMA MUHAMMADIYAH 1 JEMBER - Bahar Agus Setiawan; Sofyan Rofi; Tri Endang Jatmikowati; Siti Nursyamsiyah siti; Dahani Kusumawati (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
Self esteem conceptually has 2 main components including self competence and self liking. Self-competence is focused on describing one's own abilities, while self-liking is how far one likes or appreciates oneself. Appreciating and liking yourself is a dimension that can have a positive impact on the improvement and abilities of students both in the school environment and society in general. The aim of this research is to examine more deeply the self-liking of Muhammadiyah high school students in Jember. This study used a quantitative approach, using a structured interview instrument in the form of a questionnaire with five answer options. The results showed that the majority of students had a very good level of self-liking. There are several aspects related to the self-liking indicator aspect which has a percentage of answers that can be categorized as sufficient, namely first, the feeling of being liked by friends, second, lack of liking in the ability to express opinions, third, the feeling that students are proud of themselves. The findings of this study, although the answer options show a sufficient category, implicitly it can be understood that students have an awareness of deficiencies and do not always position themselves as over-acting or popular personalities. Based on the results of this study, it shows that the level of self-liking students has a very good category as a synergistic manifestation with good self-esteem dimensions.